Bird reproductive success and faunal habitat selection as tools for understanding the impacts of land-use management on moist highland grassland biodiversity in South Africa - Little, Ian Tchagra (Department of Biological Sciences, 2015)
It has been suggested that natural fires in these grasslands would have occurred as infrequently as every four or more years. Currently, the majority of the system is managed by livestock farmers who burn their land annually at the onset of the rainy season (early in the austral summer).